News versus market sentiments: Impact of monetary policy announcement on developed and developing countries' stock market performance - Jazib Ahmed Ansari; Danish Ahmed Siddiqui (The Journal of Entrepreneurial Finance (JEF), 2020)
This paper investigates the impact of monetary policy announcements on the performance of the stock market in twenty countries (10 Developed and 10 developing). Exchange rate changes and changes in bond yield were taken as control. Daily basis Panel data was used with daily frequency for five (5) years (2014 -2018). An impact of these selected independent variables on the stock market index is estimated using the regression model and Panel Least Square model. Monetary policy data has been run in three different lagsi.e. lag (0), lag (-1, -2, -3, -4), and lag (1, 2, 3, 4) in order to check the availability of monetary policy impact in pre and post announcement dates also, while the other variables run on a single lag. It is observed that the stock market of developedcountries has a significant relation with monetary policy announcements, however, these announcements showed an insignificance relation with the stock market index in the case of developing countries. Moreover, exchange rates seem to have a significant effect on markets of both developing and developed countries, whereas bond yield seems to have a significant effect on the stock market of Developing countries only.
Keywords: D86; G3; L26; M13; 650; monetary policy announcements; stock market index; exchange rates; bond yields; cross country; news; sentiments